Vibration and dynamic stability of composite pipelines conveying a two-phase fluid flows. (October 2019) - Khudayarov, B.A.; Komilova, Kh.M.
Abstract: The paper deals with the vibration and dynamic stability of composite pipelines conveying slug flow on viscoelastic foundations. A viscoelastic model of the theory of beams and the Winkler base model are used in the study of pipeline oscillations with a gas-containing slug flowing inside. The Boltzmann-Volterra hereditary theory of the viscoelasticity is used to describe the viscoelastic properties of the pipeline material and earth bases. The effect of gas and liquid phases flow rates, influence of tensile forces in the longitudinal direction of the pipeline, parameters of Winkler bases, parameters of singularity in the heredity kernels and geometric parameters of the pipeline on the oscillations of structures with viscoelastic properties are numerically studied. It is revealed that an increase in the length of the gas slug zone leads to a decrease in the amplitude and oscillation frequency of the pipeline. The critical rates for a two-phase slug flow are determined. It is revealed that an increase in the soil density of the bases leads to an increase in the critical rate of gas flow. It is shown that an account of viscoelastic properties of structure material and earth bases leads to a decrease in the critical flow rate. Highlights: A mathematical model has been developed for the problem of oscillations of viscoelastic pipelines conveying a two-phase slug flow. an increase in the length of the gas slug zone leads to a decrease in the amplitude and frequency of the pipeline vibrations. viscoelastic properties of the pipeline material lead to a decrease in the critical flow rate of a gas-containing two-phase liquid. an increase in the density of earth bases leads to an increase in the critical flow rate of the gas phase.